Children's Rights as Legal Subjects An Ontological and Epistemological Study in Modern Legal Philosophy - Minan Minan (Pena Justisia: Media Komunikasi dan Kajian Hukum, 2025)
Modern legal developments regarding children are no longer viewed merely as objects of protection, but as individuals with distinct legal standing. However, conceptually, the understanding of children's rights as legal subjects remains often unclear, particularly in legal practice and public policy. Therefore, a philosophical study is needed that examines the basis of existence (ontology) and the basis of knowledge (epistemology) regarding children's rights within the modern legal system. This study aims to analyze the nature of children as legal subjects and explain the epistemological basis for recognizing children's rights within the framework of modern legal philosophy oriented toward respect for human dignity and human rights principles. This study uses a qualitative method with a normative-philosophical approach. The analysis is conducted through a literature review of legal philosophy theories, international legal documents such as the Convention on the Rights of the Child (CRC), and relevant national legislation. The study shows that ontologically, children are moral and social beings who possess a complete human existence and dignity, and therefore deserve to be recognized as legal subjects. Epistemologically, the recognition of children's rights stems from modern legal rationality, which places justice and equality as universal values. This study concludes that recognizing children as legal subjects is a logical consequence of modern legal philosophy rooted in humanism and human rights. Therefore, national legal systems need to strengthen mechanisms for implementing children's rights to align with the principles of universal justice and humanitarian values.